The Rise and Fall of Leasing Syariah During The Pandemic Covid-19 - Anggraini, Misi; Rozalinda, Rozalinda; Wira, Ahmad (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this study is to analyze the rise and fall of sharia leasing during the Covid-19 Pandemic. This research uses the literature study method with a descriptive approach, a qualitative part. The data comes from magazines, books, websites, and other official documents. The results of the study show that economic development during the Covid-19 Pandemic still had an impact on sharia financing and leasing. This impact is felt from reducing assets to increasing gross premiums. However, not all obstacles to the ups and downs of sharia leasing are caused by the Covid-19 Pandemic. The existence of conventional leasing for a long time, satisfaction with services, management processes and procedures, and governance structures cause other factors. The conclusion is that the rise and fall of sharia leasing are not only caused by the Covid-19 Pandemic but also by several other factors.